Clement of Alexandria on the ‘Order’ of the Gospels - Carlson, Stephen C. (New Testament studies, 2001)
Proponents of the Griesbach hypothesis have often appealed to a tradition handed down by Clement of Alexandria in support of their position that Mark used Matthew and Luke.For example, in the 1984 Jerusalem Symposium on the Interrelations of the Gospels, the position paper for the modern form of the Griesbach hypothesis argued: ‘This one direct statement by Clement, the most highly respected Christian scholar of his day, is of more historical value than all the theories that have ever been propounded about the sequence in which the Gospels were written, including the theories of Augustine’: William R. Farmer, ‘The Statement of the Hypothesis’, The Interrelations of the Gospels: A Symposium (ed. David L. Dungan; BETL 95; Leuven: Leuven University & Peeters, 1990) 145.Other examples include William R. Farmer, The Synoptic Problem: A Critical Analysis (Dillsboro, NC: Western North Carolina, 21976) 1, 225–7, 282; William R. Farmer, ‘The Patristic Evidence Reexamined: A Response to George Kennedy’, New Synoptic Studies: The Cambridge Gospel Conference and Beyond (ed. William R. Farmer; Macon, Ga: Mercer University, 1983) 1–15; Bernard Orchard and Harold Riley, The Order of the Synoptics: Why Three Synoptic Gospels? (Macon, Ga: Mercer University, 1987) 163–8; Bernard Orchard, ‘Response to H. Merkel’, Interrelations, 603; and David L. Dungan, ‘Two-Gospel Hypothesis’, ABD 6.677. Written early in his career in the now lost Hypotyposeis, Clement's information has been preserved for us by Eusebius of Caesarea as follows:But again in those very books Clement presented a tradition of the original elders (παραδωσιν των ανεκαθεν πρεσβυτερων) about the ‘order’ of the gospels (περι της ταξεως των ευαγγελιων) in this manner: He said that those of the gospels comprising the genealogies were ‘written before’ (προγεγραϕθαι ελεγεν των ευαγγελιων τα περιεχοντα τας γενεαλογιας), that Mark had this ‘disposition’ (ταυτην εσχηκεναι την οικονομιαν): that when Peter was in Rome preaching the word openly (δημοσια) and proclaiming (εξειποντος) the gospel by the spirit, those present, who were many, entreated Mark, as one who followed him for a long time and remembered what was said, to record what was spoken; but that after he composed the gospel, he shared it (μεταδουναι) with those who wanted it; that, when Peter found out about it, he did not actively discourage or encourage it; but that John, last, aware that the physical facts were disclosed (συνιδοντα οτι τα σωματικα εν τοις ευαγγελιοις δεδηλωται) in the gospels, urged by friends, and inspired by the spirit, composed a spiritual gospel. So much for Clement. (Eusebius, H.E. 6.14.5–7)My translation, rendering the words in quotation marks as generally as possible to avoid prejudicing the interpretative issues. Other translations, however, are more specific. For example, J. E. L. Oulton translated Clement's statement for the Loeb Classical Library as follows: ‘He said that those Gospels were first written which include the genealogies’: Eusebius, The Ecclesiastical History (ed. G. P. Goold; trans. Oulton; LCL 265; Cambridge, Mass.: Harvard University, 1932) 2.47, 49.